New late Eocene and Oligocene plotopterid fossils from Washington State (USA), with a revision of "Tonsala" buchanani (Aves, Plotopteridae). (January 2022) - Mayr, Gerald; Goedert, James L.
Abstract: We report new specimens of the Plotopteridae from Washington State (USA), an area where these flightless seabirds underwent significant diversification during the late Eocene and Oligocene. To date, five plotopterid species from western Washington have been formally named. Specimens previously assigned to Tonsala buchanani Dyke, Wang, and Habib, 2011 belong to at least two, but probably even three, different species. One of these, the large-sized "Whiskey Creek specimen" from late Eocene deposits mapped as the Makah Formation, is the oldest known plotopterid and is here tentatively assigned to ? Klallamornis clarki Mayr and Goedert, 2016 . Another specimen originally referred to T. buchanani is also likely to belong to a different species and is among the most substantial records for North American plotopterids. We formally transfer T . buchanani to the taxon Klallamornis and show that the only unambiguously identified specimen of the species—the holotype—is currently poorly diagnosed from Klallamornis abyssa Mayr and Goedert, 2016, which is from coeval strata of the Pysht Formation. Although the holotype of K. abyssa is larger than that of K. buchanani, there remains a possibility that plotopterids were sexually dimorphic in size. We describe the first ungual phalanx of a plotopterid, which is referred to K. buchanani, and report previously unknown elements of the large ? K. clarki and the first records of this species from the Lincoln Creek Formation. Current data indicate that plotopterids originated in the middle or late Eocene on islands off western North America, and we hypothesize that the radiation of these birds in the North Pacific Basin may have been related to the evolution of kelp forests.